Development of a Framework for Assessing the Sustainable Index for Maintaining Low-Volume Rural Roads in India - Myakala, Raji Reddy; Sabavath, Shankar (International Journal of Sustainable Construction Engineering and Technology, 2025)
In India, low-volume rural roads (LVRRS) make up 75% of the road network and provide significant economic and social benefits. However, these advantages risk declining over time due to insufficient maintenance. The continuous deterioration of these roads leads to substantial time losses, reduced agricultural productivity, longer travel times, increased vehicle operating expenses, and a higher likelihood of accidents. To ensure sustainability, it is essential to have a thorough understanding of the interplay between social needs, economic factors, environmental concerns, and material conditions. Therefore, this study employs a quadruple-bottom-line (QBL) approach to support the development of a rural road maintenance framework focused on sustainability. Importantly, merely transferring indicators and criteria from one country's road assessment framework to another is unsuitable due to geographical variations. This study seeks to establish sustainable indicators for assessing the maintenance effectiveness of LVRRS. Experts from diverse road agencies will be involved to ensure that the indicators accurately reflect the current conditions of specific regions. This effort necessitates incorporating multiple decision-makers’ perspectives and considering various dimensions and criteria to meet the defined objectives. To create a comprehensive framework, a reliable weighting structure has been proposed to emphasize the significance of different elements related to the sustainable upkeep of rural roads. An Analytical Hierarchy Process (AHP) is utilized to assign weights within hierarchical structures across various domains. To demonstrate the practical application of this tool, four typical maintenance tasks on the major rural roads in the Warangal district have been examined as case studies. The selected projects were in or around Hanamkonda, Warangal, and Kazipet in Telangana. These projects were determined to be unsustainable out of the nine roads that were assessed using the RRSIM framework. Two other road projects were given two RRSIM stars, while the revitalization, overlay, and maintenance projects each received one.